ICTS and education: news media portrayal of e-learning in Kenya - Tuwei, David Kiplagat (Kansas State University, 2011)
From around the year 2006, the government of Kenya has committed substantial amounts of resources to build Information Communication Technologies (ICTs) around the country and in the education sector in particular, with the sole purpose of catalyzing education. This commitment has emanated from the need to increase access to education to the greater portion of the ever-growing nation’s primary and secondary school population. Some of the pressure to increase education access has also come from regional and international commitments to bodies such as the United Nations through the Millennium Development Goals (MDGs) and the New Partnership for Africa’s Development (NEPAD) through its e-school initiative. The news media have an important and potentially influential role in the discourse about the use of ICTs in education. While the news media rely on different sources for their news about ICTs and education, including politicians, central government ministers, and interest groups, policymakers, in turn, use the same media as a communication channel to relay their messages on education policy to the general public, education professionals and stakeholders. Having this symbiotic relationship between the media and its source(s) of e-learning news in mind, the purpose of this study is to examine the nature and content of the news media’s interest in e-learning and to begin to ask how it could have influenced public opinion or even the public policy-making process. Content analysis was used to audit news media content comprising 60 news articles taken from two leading online daily newspapers in Kenya. Findings from this study indicate that government officials were the most relied-upon sources of news about e-learning, while the theme of connectivity was the most discussed. The tone of the coverage was largely positive. Understanding the intersection between media coverage and e-learning ultimately enriches our understanding and knowledge of the power of journalists and news outlets in constructing the debate about educational technology. ICTs, with their efficacy in boosting education still being studied, a discussion is provided about the need for media coverage to encompass the viewpoints of all stakeholders in education and adopt a broad conceptualization of ICTs so as to have a balanced debate about ICTs and ICT projects in education.
Keywords: ICTs, Kenya, media, e-learning; Mass Communications (0708)